A method for preparing antibacterial elastic fiber material

By converting the discarded oyster shell into nano-scale powder and introducing it into polymers, antibacterial elastic fiber materials are prepared, and the problem of utilization of discarded oyster shells is solved, and the antibacterial, elastic and deodorizing effects of the material are achieved, and the cost is reduced.

CN116180267BActive Publication Date: 2025-03-18FUJIAN DAOHUA OFFSHORE ENG CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310110261.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-14
Publication Date
2025-03-18
Estimated Expiration
2043-02-14

AI Technical Summary

Technical Problem

The existing technology failed to effectively utilize discarded oyster shells, failed to reach nano-scale powders, and did not make breakthroughs in the field of antibacterial elastic fiber materials.

Method used

The discarded oyster shell is converted into nano-scale powder by calcining, crushing and other processes, and introduced into polymers, and antibacterial elastic fiber materials are prepared by blending, extrusion, granulation and fiber formation processes.

Benefits of technology

The prepared materials have excellent antibacterial properties, elastic properties and deodorization adsorption effects, which solves environmental pollution problems and reduces the cost of the polymer industry.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116180267B_ABST
    Figure CN116180267B_ABST
Patent Text Reader

Abstract

A method for preparing an antibacterial elastic fiber material belongs to the modification technology of high molecular polymer materials. The present invention uses waste oyster shells, elastomer compatibilizers, SiO2 aerogels, and PET materials as raw materials. First, nano-scale oyster shell powder is prepared by pre-treating, calcining, crushing, and grinding the oyster shells; secondly, the powder is melt-blended with PET, elastomer compatibilizers, and SiO2 aerogels in a certain proportion, and the uniform melt blend is extruded and granulated, cooled and dried, and sliced; finally, the slices are melted again, extruded and drawn into fibers for use in the textile field. The present invention processes waste oyster shells in depth, turning waste into treasure, and applies them to polymer modification. The modified fiber materials can show good antibacterial properties, elastic properties, and deodorizing and adsorption effects, and can reduce production costs and save petroleum resources. Since the product has antibacterial properties, it also actively promotes the research of new functional materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of high molecular polymer modification, in particular to an oyster shell modified high polymer fiber material and a preparation process thereof, in particular to a fiber for textiles, which has certain antibacterial and elastic properties. Background Art

[0002] Oysters are known as "milk in the sea" and are widely loved by people because of their delicious meat. The mass of oyster shells accounts for about 70% to 90% of the total mass of oysters. The calcium carbonate content in the shells is as high as 88.59% to 99.20%, and it contains a small amount of trace elements and organic matter. It is a valuable inorganic salt resource. However, most oyster shells are discarded as a type of marine waste. On the one hand, they occupy valuable land and tidal flat resources. On the other hand, the organic matter in the discarded oyster shells is oxidized and corrupted in the air, breeding a large number of pathogenic microorganisms, causing quite serious environmental pollution and waste of solid waste resources. Therefore, the resource utilization of solid waste has become a hot research topic in the current society.

[0003] As a new material developed in the 20th century, polymer materials have excellent performance and a wide range of applications, but there are still many difficulties that need to be overcome, such as poor thermal stability, creep, poor aging resistance, strength limitations, etc. Therefore, it is necessary to modify polymer materials to give products new properties or reduce costs without sacrificing performance to the minimum, significantly improve expected performance, further broaden the application field of polymer materials, and improve their application value.

[0004] Currently, the existing technology has not been able to produce nano-level oyster shell powder, and the research on turning oyster shells into "treasure" and applying them in the field of antibacterial elastic fibers has not yet been developed.

[0005] The present invention converts discarded oyster shells into nano-scale oyster shell powder through calcination, crushing and other processes, introduces the modified nano-scale oyster shell powder, elastomer compatibilizer, silica and polymer for blending, extrusion, granulation and fiberization, which can be applied to the textile field, and the fabric has good antibacterial properties. As people's requirements for environmental hygiene are increasing, the application of antibacterial materials has also received more extensive attention, and has extremely broad application prospects in the fields of medical care, daily necessities, military clothing and the like, which has greatly promoted the development of new functional materials. Summary of the invention

[0006] The purpose of the present invention is to solve the above problems in the prior art and provide a method for preparing an antibacterial elastic fiber material, which has excellent antibacterial and elastic properties and can be used in the textile field.

[0007] In order to achieve the above object, the present invention adopts the following technical scheme:

[0008] A method for preparing an antibacterial elastic fiber material comprises the following steps:

[0009] 1) Oyster shell pretreatment: air drying, aging, cleaning, and impurity removal;

[0010] 2) Preparation of nano-sized oyster shell powder: high temperature calcination, coarse grinding, and fine grinding;

[0011] 3) Polymer modification: PET (polyethylene terephthalate) material and elastomer compatibilizer were vacuum dried, and then nano-sized oyster shell powder, SiO 2 Aerogel, PET material and elastomer compatibilizer are melt blended; by weight ratio, the nano-sized oyster shell powder accounts for 0.1wt% to 1.0wt%, the elastomer compatibilizer accounts for 1wt% to 20wt%, and SiO 2 Aerogel accounts for 0.1wt% to 1.0wt%, and the rest is PET material;

[0012] 4) Granulation: melt extrusion, cooling, and pelletizing;

[0013] 5) Fibering: drying and slicing, secondary melting, and drawing into fibers;

[0014] 6) Post-processing: dyeing and weaving to obtain finished fabrics.

[0015] In step 1), the oyster shell pretreatment method is: the oyster shell is naturally air-dried, aged for 4 to 9 months, cleaned with clean water or seawater to remove surface impurities, and then aged for 1 to 2 months.

[0016] In step 2), the high temperature calcination is carried out in stages, firstly the temperature is raised to 500-700° C. for calcination for 1-2 hours, then the temperature is lowered to 300-500° C. for calcination for 2-4 hours, and finally the temperature is raised to 800-1100° C. for calcination for 2-4 hours.

[0017] In step 2), the fine grinding is to finely grind the coarse oyster shell powder using a planetary ball mill to make the particle size of the oyster shell powder reach less than 1 μm.

[0018] In step 3), the nano-sized oyster shell powder accounts for 0.1wt% to 0.4wt% by weight; the elastomer compatibilizer accounts for 5wt% to 15wt%; SiO 2 The proportion of aerogel is preferably 0.2 wt% to 0.4 wt%, and the rest is PET material.

[0019] In step 3), the temperature of melt blending is 255-270° C., the blending time is 3-5 min, and the blending speed is 40-70 rpm.

[0020] In step 3), the elastomer compatibilizer includes a polyolefin elastomer (POE) grafted with maleic anhydride, a SEBS (triblock copolymer: polystyrene as the end and ethylene-butylene copolymer added in the middle) grafted with maleic anhydride, or a polyolefin elastomer modified with glycidyl methacrylate (GMA).

[0021] In step 5), the temperature of the secondary melting is 255-270°C.

[0022] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:

[0023] 1. The material prepared by the present invention has excellent antibacterial properties, elastic properties and deodorizing adsorption effects, and actively promotes the research of new functional materials.

[0024] 2. The present invention can alleviate many environmental problems caused by the disposal of oyster shells, such as: accumulation of environmental waste; water and ocean pollution caused by illegal landfill and microbial activities; odor problems caused by reduced attention to cheap disposal; expensive waste management costs; inappropriate recycling.

[0025] 3. The present invention uses oyster shells as fillers, which greatly reduces the cost of the polymer industry; since synthetic resin is a petrochemical product, the usage is reduced, which can save non-renewable energy. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is one of the electron microscope images of the nano-sized oyster shell powder prepared in Example 1;

[0027] Figure 2 This is the second electron microscope image of the nano-sized oyster shell powder prepared in Example 1. DETAILED DESCRIPTION

[0028] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention clearer and more understandable, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them.

[0029] Example 1

[0030] A method for preparing an antibacterial elastic fiber material comprises the following steps:

[0031] 1) Oyster shell pretreatment: The oyster shells are naturally air-dried and aged for 6 months, then cleaned with clean water or seawater to remove surface impurities, and then aged for another 2 months;

[0032] 2) Preparation of nano-sized oyster shell powder: high-temperature calcination, coarse grinding, and fine grinding; the high-temperature calcination is carried out in stages, firstly the temperature is raised to 600°C for calcination for 2 hours, then the temperature is lowered to 400°C for calcination for 4 hours, and finally the temperature is raised to 900°C for calcination for 4 hours; the coarse grinding is to grind the oyster shell into fine powder by physical powder technology and pass through a 600-mesh sieve; the fine grinding is to grind the oyster shell coarse powder by a planetary ball mill using ball milling technology to make the oyster shell powder particle size reach less than 1 μm; see Figures 1-2 , is the nano-sized oyster shell powder prepared in this embodiment;

[0033] 3) Polymer modification: PET slices were vacuum dried at 120°C overnight, and the elastomer compatibilizer was vacuum dried at 60°C for 16 h. 2 Aerogel, PET material and elastomer compatibilizer were melt blended at a melting temperature of 260 ° C and a blending time of 3 min. The blending speed was 60 rpm. By mass ratio, the nano-sized oyster shell powder accounted for 0.4 wt%, the elastomer compatibilizer accounted for 5 wt%, and SiO 2 The aerogel accounts for 0.2wt%, and the rest is PET material; in this embodiment, the PET material uses recycled polyethylene terephthalate (r-PET) material;

[0034] The elastomer compatibilizer is made of maleic anhydride grafted modified polyolefin elastomer (POE), which can give the material a certain elastic deformation and slow down the creep effect of the polymer material; the oyster shell powder added in the process is slightly more, and the main component of the oyster shell powder after high-temperature calcination is calcium oxide, wherein calcium oxide releases oxygen-containing free radicals for antibacterial, which can enhance its antibacterial effect; a certain amount of SiO 2 Aerogel acts as a lubricating material;

[0035] 4) Granulation: After the blending is completed, the composite masterbatch is extruded through a twin-screw extruder, uniformly extruded into a cooling tank, cooled with tap water, and pelletized to obtain slices;

[0036] 5) Fibering: Pre-dry the slices to prevent the moisture in the slices from hydrolyzing the polyester and affecting the spinning performance and fiber quality. The slices must be dried to reduce the moisture content to below 0.01%; heat in the screw and melt for the second time at a temperature of 265°C; and spray out through the spinneret holes with a spinneret diameter of 0.2mm;

[0037] 6) Post-processing: dyeing and weaving to obtain finished fabrics.

[0038] The material prepared by the present invention has excellent antibacterial properties and can also exhibit certain elastic properties, but has a relatively rough feel. It can be put into production and used as a wear-resistant antibacterial material, such as conveyor belts, floor mats, etc.

[0039] Example 2

[0040] The difference between this embodiment and embodiment 1 is that in step 3), the mass proportion of nano-sized oyster shell powder is 0.2wt%, the mass proportion of elastomer compatibilizer is 10wt%, and the mass proportion of SiO 2 The mass proportion of aerogel is 0.4wt%, and the rest is PET material; the melting temperature is 265°C, the blending time is 4min, and the rotation speed is 70rpm.

[0041] Among the process parameters mentioned above, the increase in the proportion of elastomer compatibilizer can give the material excellent elastic properties.

[0042] The material obtained under this process parameter not only has good antibacterial and elastic properties, but also has good 2 The addition of a slightly larger proportion of aerogel can also show excellent ductility and can be applied to materials that require antibacterial properties and elasticity, such as sports quick-drying clothes, environmentally friendly handbags, etc.

[0043] Example 3

[0044] The difference between this embodiment and embodiment 1 is that in step 3), the mass proportion of nano-sized oyster shell powder is 0.3wt%, the mass proportion of elastomer compatibilizer is 5wt%, and the mass proportion of SiO 2 The mass proportion of aerogel is 0.3wt%, and the rest is PET material; the melting temperature is 260°C, the blending time is 4min, the rotation speed is 60rpm, and the elastomer compatibilizer is GMA-modified polyolefin elastomer. Since GMA has high activity, it can effectively improve the sensitivity to notch strength in the material, has higher processing fluidity, can reduce product processing defects and improve production efficiency.

[0045] The material obtained by the above process parameters has good antibacterial properties, elastic properties and processability, and has the potential to be used in the field of daily use materials, such as shirts, scouring pads, etc.

[0046] Comparative Example 1

[0047] The difference between this comparative example and Example 1 is that in step 2), oyster shell powder is prepared without high-temperature calcination. The main steps include preliminary crushing, coarse grinding, and fine grinding; the coarse grinding is to grind the oyster shell into fine powder by physical powder technology and pass through a 600-mesh sieve; the fine grinding adopts ball milling technology, and finely grinds the oyster shell coarse powder with a planetary ball mill to make the oyster shell powder particle size reach less than 1 μm. The effect of oyster shell powder without high-temperature calcination on the antibacterial properties of the modified polymer material is analyzed.

[0048] Comparative Example 2

[0049] The difference between this comparative example and Example 1 is that in step 2), nano-scale oyster shell powder is prepared: high-temperature calcination, coarse grinding, and fine grinding; high-temperature calcination does not use segmented calcination, and the temperature is directly raised to 900°C for calcination for 10 hours; the coarse grinding is to grind the oyster shell into micro powder by physical powder technology and pass through a 600-mesh sieve; the fine grinding uses ball milling technology to finely grind the oyster shell coarse powder with a planetary ball mill to make the oyster shell powder particle size reach less than 1 μm. The effect of oyster shell powder without segmented calcination on the antibacterial properties of the modified polymer material is analyzed.

[0050] Comparative Example 3

[0051] The difference between this comparative example and Example 1 is that step 1) and step 2) are omitted, and in step 3), nano-sized oyster shell powder is not added during the polymer modification process. The effect of adding nano-sized oyster shell powder on the antibacterial properties of the modified polymer material is analyzed.

[0052] The performance parameters of the above examples and comparative examples are shown in Table 1 below:

[0053] Table 1

[0054]

[0055] Among them, the antibacterial properties of the above-mentioned composite materials are qualitatively and quantitatively analyzed by the disc diffusion method. First, the bacteria were inoculated into tryptic soy broth and nutrient broth for 24 hours to prepare bacterial (Staphylococcus aureus and Escherichia coli) suspension cultures. Secondly, the microbial suspension was evenly spread on the nutrient agar plate with a sterile cotton swab. Subsequently, 5 mg of sample (Examples 1, 2, 3, Comparative Examples 1, 2, 3) was placed in the center of a 100 mm culture dish. The sample was incubated at 37°C for 24 hours. The inhibition zone generated around it was evaluated. The size of the inhibition zone refers to the diameter of the inhibition zone of the modified composite material in the culture dish containing Staphylococcus aureus.

[0056] The various performances and principles involved in the present invention are as follows:

[0057] 1. The internal structure of the oyster shell presents a loose porous structure and an open network structure, which provides a larger specific surface area. After high-temperature calcination, this structure remains intact. At the same time, CO 2 The escape of leads to a large number of mesoporous structures, which makes the oyster shell powder obtained by the above process have excellent adsorption performance and an easy-to-blend structure, which can enhance the deodorizing effect of the powder.

[0058] 2. Since calcium oxide is an inorganic filler with good hydrophilicity, and high molecular polymers are hydrophobic, if added directly, it will lead to uneven powder distribution and poor compatibility. The aggregated large particles will become stress concentration points of the material, and then become the weak link of product performance, which not only limits the powder filler, but also seriously affects the mechanical properties of the material. Therefore, the present invention needs to add silicon dioxide during the blending process to play a lubricating effect and make the powder evenly dispersed.

[0059] 3. Theoretically, PET is polar, while elastomer compatibilizers are generally non-polar. There is usually strong tension between the two phases at the interface. In order to increase the capacity of the system, the elastomer is generally grafted with maleic anhydride. PET and the maleic ring can react to form a chemical bond between the two phases, thereby enhancing the toughness of the material and improving the impact resistance. Glycidyl methacrylate (GMA) can also be used to modify the elastomer. Since GMA has high activity, its application in polyester materials can effectively improve the sensitivity to notch strength, has higher processing fluidity, can reduce product processing defects, and improve production efficiency.

[0060] 4. The introduction of oyster shell powder gives the material antibacterial properties. After high temperature treatment, the biocompatibility of CaO gives it new vitality as a bactericidal material. The two main mechanisms of action of CaO are the alkaline effect and the generation of reactive oxygen species (ROS) on the surface of CaO. CaO hydrates with water to form hydroxide (pH>11), OH - Capturing electrons on the bacterial membrane hinders the respiratory electron transport chain, which is the first major antibacterial mechanism. ROS with strong oxidative activity react with proteins, DNA and lipid membranes to destroy bacterial structures, which is the second mechanism. Another prominent factor of CaO is that it produces Ca 2+ , Ca 2+ The charge balance of the bacterial cell membrane is destroyed, leading to bacterial death.

[0061] 5. The present invention significantly improves the impact resistance and enhances the toughness of the material by blending a certain proportion of an elastomer compatibilizer and PET. The principle is that under the action of external forces, the elastomer compatibilizer is dispersed in the polymer matrix, and the elastomer particles dispersed in the matrix exist as stress concentration points. The elastomer particles generate three-dimensional tension and act in the surrounding resin phase. This tension weakens the internal action of the elastomer, further causing the interior of the particles to become hollow, the surface of the matrix to become silvery, and the material to be impacted and separated from the matrix after the elastomer particles are added. These changes will cause the volume of the material to expand and absorb part of the impact energy. At the same time, if multiple stress fields are superimposed and exceed a certain value, the matrix will produce highly oriented shear bands. In this process, the material absorbs a large amount of impact energy.

Claims

1. A method for preparing an antibacterial elastic fiber material, characterized in that The following steps are involved: 1) Oyster shell pretreatment: air drying, aging, cleaning, and impurity removal; 2) Preparation of nano-sized oyster shell powder: high temperature calcination, coarse grinding, and fine grinding; 3) Polymer modification: The PET material and the elastomer compatibilizer are vacuum dried, and then the nano-sized oyster shell powder, SiO2 aerogel, PET material and the elastomer compatibilizer are melt-blended; by mass ratio, the nano-sized oyster shell powder accounts for 0.1wt% to 1.0wt%, the elastomer compatibilizer accounts for 1wt% to 20wt%, the SiO2 aerogel accounts for 0.1wt% to 1.0wt%, and the rest is PET material; 4) Granulation: melt extrusion, cooling, and pelletizing; 5) Fibering: drying and slicing, secondary melting, and drawing into fibers; 6) Post-processing: dyeing and weaving to obtain finished fabrics; In step 2), the high temperature calcination is carried out in stages, firstly the temperature is raised to 500-700°C for calcination for 1-2 h, then the temperature is lowered to 300-500°C for calcination for 2-4 h, and finally the temperature is raised to 800-1100°C for calcination for 2-4 h; In step 2), the fine grinding is to finely grind the coarse oyster shell powder using a planetary ball mill to make the particle size of the oyster shell powder reach less than 1 μm.

2. The method for preparing an antibacterial elastic fiber material according to claim 1, characterized in that: In step 1), the oyster shell pretreatment method is: the oyster shell is naturally air-dried, aged for 4 to 9 months, washed with clean water or seawater to remove surface impurities, and then aged for another 1 to 2 months.

3. The method for preparing an antibacterial elastic fiber material according to claim 1, characterized in that: In step 3), by mass ratio, the proportion of nano-sized oyster shell powder is 0.1wt% to 0.4wt%; the proportion of elastomer compatibilizer is 5wt% to 15wt%; the proportion of SiO2 aerogel is 0.2wt% to 0.4wt%, and the rest is PET material.

4. The method for preparing an antibacterial elastic fiber material according to claim 1, characterized in that: In step 3), the temperature of melt blending is 255-270°C, the blending time is 3-5 min, and the blending speed is 40-70 rpm.

5. The method for preparing an antibacterial elastic fiber material according to claim 1, characterized in that: In step 3), the elastomer compatibilizer is made from maleic anhydride grafted modified polyolefin elastomer, or is made from maleic anhydride grafted modified SEBS, or is made from GMA modified polyolefin elastomer.

6. The method for preparing an antibacterial elastic fiber material according to claim 1, characterized in that: In step 5), the temperature of the secondary melting is 255-270°C.

Citation Information

Patent Citations

  • Shell powder, preparation method thereof, modification method thereof and application thereof

    CN105053002A

  • Special antibacterial, warm-keeping and high energy efficiency composite fiber

    TWM613013U